2021
DOI: 10.22620/agrisci.2021.31.008
|View full text |Cite
|
Sign up to set email alerts
|

Helminths and helminth communities of Carassius gibelio (Bloch, 1782) from the Panicheri Reservoir, Aegean Water Basin, Bulgaria

Abstract: Ecologoparasitological research was done based on the helminths and helminth communities of the Prussian carp (Carassius gibelio (Bloch, 1782)) from the freshwater ecosystem of the Panicheri Reservoir, Aegean Water Basin, Bulgaria. As a result of the examined nine specimens of the Prussian carp, two species of helminths were found: Ligula intestinalis (Linnaeus, 1758), larvae and Pomphorhynchus laevis (Müller, 1776). The dominant structure of the helminth communities was determined. The Panicheri Reservoir is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Gravel bottom is its preferable substratum. Algae and crustaceans are the dominant food items for young individuals and insects, insect larvae and sh for adults (Fröse and Pauly 2018; Kirin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravel bottom is its preferable substratum. Algae and crustaceans are the dominant food items for young individuals and insects, insect larvae and sh for adults (Fröse and Pauly 2018; Kirin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The species' diet varies depending on the life stage, as juveniles feed mainly on phytoplankton, zooplankton and crustaceans, while adults predate on insects, insects' larvae, sh, etc. (Kirin et al 2019;Kolev 2021). Dace has different behavioral patterns during the summer and winter periods (Kolev 2021).…”
Section: )mentioning
confidence: 99%
“…The Veleka River has been studied for Pb and Zn content in sediments, sh and their parasites. A high concentration of zinc in the sediment and a higher Pb content in the parasites were found (Kirin 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Due to its location, the aquatic ecosystem is assumed to have low anthropogenic pressure, but as a result of the active tourist season, the discharge of wastewater from a sewage treatment plant and the cultivation of nearby agricultural areas, it is one of the polluted rivers in the area. The literature survey found that a comprehensive study of the Karagach river has not been conducted yet and it shows data on Veleka River and Burgas Lake Vaya in Southeastern Bulgarian Black Sea region (Falah et al 2019;Kirin 2014).…”
Section: Introductionmentioning
confidence: 99%